PENGARUH PROMO GRATIS ONGKIR, CUSTOMER REVIEWlDAN DISKON TERHADAP KEPUTUSAN PEMBELIAN MELALUI APLIKASI SHOPEE - Dara Melfaliza; Ahmad Nizam (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2022)
This study aims to examine the effect of free shipping promos, customer reviews and discounts on purchasing decisions through the shopee application. The population used is the students of the Faculty of Economics and Business, Syiah Kuala University with a sample of 173 respondents determined by purposive sampling technique. The data used are primary data obtained from distributing questionnaires to respondents. This study uses multiple linear regression as the method of analysis. The results showed that either partially or simultaneously, the variables of free shipping promos, customer reviews and discounts had an effect on purchasing decisions through the shopee application for students of the Faculty of Economics and Business, Syiah Kuala University. Thus, consumers do not object to making purchasing decisions because they do not have to pay more for shipping costs.